Men's triathlon correlation between the phases and result in the Olympic Games in London 2012 - Fernandez Revelles, A. B.; Ramirez-Granizo, I. A.; Castro-Sanchez, M.; Padial Ruz, R. (Journal of Human Sport & Exercise, 2018)
Introduction: Triathlon is a sport that is composed of the combination of three phases of competition. The most widespread triathlon is the Olympic, and is used in the Olympic Games, consists of swim, 1.5 km, bike 40 km and run 10 km. Aims: To determine the influence of the duration and order of the phases with the final result of the test in the male triathlon in the Olympic Games London 2012. Method: We analyzed the data of 50 athletes who finished. Results and conclusions: The final result is not determined either by the order of the phases, nor by the duration of these, the least influential phase has been Bike without correlation with final result; being the one that has occupied the most time with 53.76%; The most influential phase was the Run phase with rs = .913; and p = .000; and R2 = .833 and with duration 28.93%.